Treatment of central sensitization in patients with chronic pain: time for change?. (2nd November 2019) - Nijs, Jo; Leysen, Laurence; Vanlauwe, Johan; Logghe, Tine; Ickmans, Kelly; Polli, Andrea; Malfliet, Anneleen; Coppieters, Iris; Huysmans, Eva
ABSTRACT: Introduction : Given our improved understanding of the role of central sensitization (CS) in many patients with chronic pain, it seems rational to account for CS during treatment. Areas covered : First, the treatment rationale based on the complex mechanisms underlying CS in patients having chronic pain is presented. Second, emphasis is given to explaining the concept of CS when providing treatment, as well as why patients and clinicians should focus on long-term rather than short-term treatment effects. Third, possible pharmacological and non-pharmacological treatment options are discussed. Expert opinion : Centrally acting drugs such as tricyclic compounds, serotonin-norepinephrine reuptake inhibitors, and α2 δ ligands each target mechanisms that are often dysfunctional in patients having chronic pain and CS, but decades of clinical practice and clinical trials have not resulted in satisfactory outcomes. This comes as no surprise; CS comprises complex psycho-neuro-immunological interactions, while each of the tested drugs targets one or two of those mechanisms from a purely biomedical viewpoint. Clinicians willing to take CS into account should design an individually tailored multimodal treatment plan comprising pain neuroscience education, cognition-targeted exercise therapy, sleep management, stress management, and/or dietary intervention.